Farmers' Willingness to Pay for Bio-slurry Fertilizer in Central Java - Malinda Aptika Rachmah; Dwidjono Hadi Darwanto; Jangkung Handoyo Mulyo (Agro Ekonomi, 2020)
Bio-slurry is the residual product of biogas processing waste through the decomposition process without oxygen (anaerobic). Bio-slurry can be used as organic fertilizer for agricultural land. This study aims to: 1) assess the value of willingness to pay (WTP) for bio-slurry fertilizer, 2) find factors affecting farmer’s willingness to pay (WTP) of bio-slurry fertilizer. The research was carried out from January to February 2020 in Central Java. Determination of the location is purposive based on the farmers in Magelang and Demak Regency that have utilized biogas waste to be organic fertilizer and had been commercialized. Primary data were obtained from 80 farmers using purposive sampling, with the aid of questionnaire. Data analysis using contingent value method (CVM) to evaluate the farmer’s willingness to pay and logistic regression to analyze its determinant factors. The result showed that farmer’s willingness to pay (WTP) rate of bio-slurry fertilizer was IDR. 937,5/kg, which was above the market price. The determinant factors are farm income, education, price, and experience using organic fertilizer positively related to farmers’ willingness to pay bio-slurry fertilizer whereas land area negatively related to farmers’ willingness to pay bio-slurry fertilizer. The value of willingness to pay show the opportunity for bio-slurry fertilizer to survive in market by taking into account continuity of production and quality.